Analysis of viscosity test conditions for crumb-rubber-modified asphalt. (10th June 2020) - Ding, Zhan; Li, Peilong; Zhang, Jing; Bing, Hui; Yue, Xiangjing
Highlights: The viscosity of CRMA were test using different rotors under different conditions. The viscosity test principle and variation law were analyzed using rheological principles. The influence of rotors and speeds on CRMA viscosity and torque were discussed. The relation between torque and viscosity was established. The viscosity test Conditions of CRMA are recommended. Abstract: Brookfield's rotational viscosity has been widely applied for characterizing the rheological behavior of crumb-rubber-modified asphalt (CRMA). However, the test conditions greatly influence the viscosity results of CRMA. Effectively choosing the rotor and rotational speed for CRMA remains unclear. The rotors with different specifications were selected to test 180 °C viscosity of CRMA with different rubber contents under different rotational speeds. Meanwhile, the viscosity corresponding to 50% was obtained by interpolation, and the test principles and variation law of asphalt viscosity were analyzed by applying rheological principles. This investigation analyzed the influence of rotors and speeds on CRMA viscosity and torque during viscosity testing and established the relation between torque and viscosity. Results show that rotor model and test speed significantly affect CRMA viscosity and that of the base asphalt is not affected. Torque and speed has a power- and quadratic-function relation with CRMA viscosity, respectively, whereas there is a linear relation between torque and speed. The rotor and speed recommendations for 180 ℃-viscosity of CRMA with different test accuracy requirements are given, ensuring the effectiveness and comparability of the CRMA viscosity test results.